Characterization of Two Domestic Goat Breeds in Duhok Province / Iraq Using Microsatellites - Mohammed, Ahmed Basheer (Science Journal of University of Zakho, 2013)
In this study, a molecular‒based technique was employed to characterize two Iraqi goat breeds. For this, thirty blood samples were obtained from two Iraqi indigenous goat breeds (Native and Merzi goat) in Duhok province. Genomic DNA was extracted, out of 8 microsatellites, 6 microsatellites were amplified and produced bands in polymerase chain reactions (PCR). PCR products were subjected to 1.5% agarose gel electrophoresis for fast and easy detection of successful amplification. Then, the PCR products were subjected to 6% Polyacrylamide electrophoresis and stained with silver nitrate. Many distinct alleles were observed that they can be indicative of possible breed marker.Close genetic distance was observed between Native and Merzigoat (D=0.1667). These results can be used to establish national conservation and breed improvement strategies.
Keywords: Duhok; microsatellites; Merzi and Native goats